Universal principles of art : 100 key concepts for understanding, analyzing, and practicing art - Parks, John A., 1952- (Rockport Publishers, 2015)
Universal Principles of Art is a comprehensive reference for all artists, and a follow up to Rockport Publishers' best-selling Universal Principles of Design.